Assessing the impact of malignant thyroid nodules on the efficacy of radiofrequency ablation: a single-center prospective study - Liu, Huan; Shi, Chuanke; Yan, Zhideng; Luo, Ming (Frontiers in Endocrinology, 2025)
BackgroundRadiofrequency ablation (RFA) is currently the mainstay of treatment for thyroid nodules (TNs), with indications that extend from initially benign nodules and micropapillary thyroid carcinoma to current low-risk papillary thyroid carcinoma. Our study aims to evaluate the impact of malignant nodules on the efficacy of RFA.MethodsA total of 970 eligible patients were divided into benign and malignant group. We analyzed whether the efficacy of RFA differed between the two groups in terms of TNs volume, volume reduction ratio (VRR), technical effectiveness (TE), complete ablation (CR), and regrowth rate, and used multivariate logistic and linear regression to assess whether malignant nodules were a risk factor for its efficacy.ResultsThe TE value was higher in the benign group than in the malignant group (81.7% vs. 70.5%, p=0.002 < 0.052). However, after excluding patients with less than 1 year of follow-up, the adjusted TE values were not significantly different between the two groups. The malignant group had a higher CR than the benign group (43.6% vs. 9.7%, p < 0.001) and its CR time was shorter (14.09 ± 11.50 months vs. 21.75 ± 13.18 months, p < 0.001). The regrowth rate was higher in the benign group than in the malignant group. Multivariate logistic analysis showed that there was no difference between the two groups in TE and regrowth, however, the benign group had a lower CR than the malignant (adjusted OR = 0.100, 95%CI 0.055- 0.181, P<0.001). Multivariate linear regression analysis showed that the VRR in the malignant group was lower than that in the benign at years 1 and 2 after RFA, but there was no difference after 2 years.ConclusionMalignant thyroid nodules do not affect the efficacy of radiofrequency ablation. Although their early target regression is slower after RFA, there is no difference in long-term outcomes, and they are more likely to achieve complete regression.